"I'm a Little Black Boy and I Don't Know My Place": Phil Lynott and the Black Atlantic. Issue 1 (2nd January 2022) - Bannister, Matthew
ABSTRACT: This essay uses Paul Gilroy's The Black Atlantic to examine Phil Lynott, of '70s Irish hard rock band Thin Lizzy. Lynott's "mixed" lineage (half Caribbean black, half Irish) relates to Gilroy's black diaspora in terms of parentage and popular music the latter being central to Gilroy's argument about the articulation of black experience of trauma and dislocation in creative and other forms. Discussion of gender in popular music intersects with discourses that highlight "excessive" masculinity in nonwhite subjects. The essay considers alternative approaches to masculinity: gender performativity, homosocial interaction, and punk, while employing Black Atlantic concepts of antiphony and rhythmic complexity to investigate the band's music.